Influence of Open Tendering on the Performance of County Government of Garissa, Kenya - Jane Chemtai; Dr. Simon Nyakwara (IJRDO - Journal of Social Science and Humanities Research, 2020)
In Garissa County, a total of 593 projects were implemented across the county. Out of this, 261 projects were implemented within CIDP while 332 projects were implemented outside the current CIDP 2013-2017. The purpose of the study was to establish the influence of procurement practices on performance of Garissa County government. The objectives of the study were to; to establish the influence of open tendering on the performance of county government of Garissa, to determine the influence of restricted tendering on the performance of county government of Garissa, to find out the influence of single sourcing on the performance of county government of Garissa and to determine the influence of request for quotations on the performance of county government of Garissa. The study was guided by Agency, Auction and theory of constrain The study adopted mixed method approach, where for qualitative data the design that was applied was phenomenological, while for quantitative data, it was descriptive survey design, the researcher later triangulated these two data sets concurrently within the same time frame. The study targeted 222 employees of Garissa county Government working in the head office. The sample size of 179 respondents will be determined by Magnani, (1997) formula. Questionnaires were used as the data collection tools. Piloting was done in Wajir County on 10% of the sample size, the instruments were validated by the supervisors and reliability was determined through test retest technique thereafter Cronbach alpha coefficients was determined using 0.7 internal efficiency. The data was analyzed using statistical package for social sciences (SPSS) Version 21 computer software, where descriptive and inferential statistics were derived involving formulation of regression models; analysis of the coefficient of determination of the models and standard errors of the model’s parameters were used. To analyze the qualitative data obtained, themes were derived and presented in narrative form. The study established that Garissa county government can only create a competitive open tendering process by providing equal opportunities for application, treatment of suppliers must be fair and all protocols set must be followed by the interesting parties. It should aim at improving value delivery to customers, eliminating waste and getting all the stakeholders involved in the value creation process. The county government should find a means to ensure that quotations are submitted in time and the evaluation process should cost efficient as possible. Request for quotation influences supply chain by reducing lead time and there is no need to prepared solicitation documents or advertise requirements.